Law No. 76 of the year 2016 On Amending Certain Provisions of Law No. 231 of the year 1996 Concerning Some Stipulations Regulating the Employment of Egyptians by Foreign Entities = قانون رقم 76 لسنة 2016 بتعديل بعض أحكام القانون رقم 231 لسنة 1996 ببعض الأحكام الخاصة بتنظيم عمال مصريين لدى الجهات الأمنية - The Middle East Library for Economic Services (The Middle East Library for Economic Services, 2025)
English & Arabic